2022
DOI: 10.3390/biomedicines10020445
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Canonical Link between Non-Coding RNAs and Cardiovascular Diseases

Abstract: Cardiovascular diseases (CVDs) are among the top leading causes of mortality worldwide. Besides canonical environmental and genetic changes reported so far for CVDs, non-coding RNAs (ncRNAs) have emerged as key regulators of genetic and epigenetic mechanisms involved in CVD progression. High-throughput and sequencing data revealed that almost 80% of the total genome not only encodes for canonical ncRNAs, such as micro and long ncRNAs (miRNAs and lncRNAs), but also generates novel non-canonical sub-classes of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…ROS can also directly oxidize certain miRNAs and hydroxylate guanine to generate 8-oxo-7,8-dihydroguanosine (8OHG), altering its structure and stability [148]. Recent studies have found that miRNA-specific position 8-oxoguanine (O8G) modification can alter the target mRNA of miRNA and play an epigenetic regulatory role [149,150]. ROS can affect miRNA maturation by downregulating the expression of Dicer and posttranslationally modifying argonaute-2 (AGO2) and altering Dicer and AGO2 activities [151].…”
Section: Ros Regulate Mirna Expressionmentioning
confidence: 99%
“…ROS can also directly oxidize certain miRNAs and hydroxylate guanine to generate 8-oxo-7,8-dihydroguanosine (8OHG), altering its structure and stability [148]. Recent studies have found that miRNA-specific position 8-oxoguanine (O8G) modification can alter the target mRNA of miRNA and play an epigenetic regulatory role [149,150]. ROS can affect miRNA maturation by downregulating the expression of Dicer and posttranslationally modifying argonaute-2 (AGO2) and altering Dicer and AGO2 activities [151].…”
Section: Ros Regulate Mirna Expressionmentioning
confidence: 99%
“…For instance, because of miR-451 precursor’s cleavage by Drosha/Dgcr8, the product is not long enough to cleave by Dicer. Hence, Pre-miR-451 was cleaved by unknown enzymes and then loaded into the Ago-RISC complex ( Natarelli and Weber, 2022 ). Furthermore, there are some miRNAs localized in the nucleus through specific nucleotide motifs.…”
Section: Non-coding Rnas For the Treatment And Diagnosis Of Familial ...mentioning
confidence: 99%
“…Besides the cytoplasm, miRNAs also localize to the nucleus [2,7]. They modulate gene expression [2,8,9] and potentially a subset of alternative splices [10][11][12].…”
Section: The Links Between Mirnas and Gene Regulationmentioning
confidence: 99%